(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Rapid developments in genetics studies, which often include ethical dilemmas and societal implications, make students’ understanding of genetics-related concepts and making informed decisions on genetics-related issues reflexively vital. The socioscientific issue-based strategy (SSI) is a learning strategy that places the learning of science content within a social context, which also involves moral reasoning or ethical considerations in deciding how to resolve those issues. After learning genetics with the SSI, 140 secondary students’ understanding and reflective thinking of genetics concepts were evaluated. The results were promising, showing a significant main effect on students’ knowledge and reflective thinking. This significant improvement is a hopeful sign for the future of science education, as it emphasizes the importance of the SSI strategy in preparing students for real-world genetic issues.